Pertimbangan Orang Tua Dalam Memilih Taman Kanak-Kanak - Kurniawan, Diki (NOKEN : Jurnal Pengelolaan Pendidikan, 2023)
Parents' considerations in choosing a school for their child, especially early childhood education in the kindergarten program, are activities that must be carried out by parents before enrolling their child in school. It is intended that the education that children receive is in accordance with their needs so that it can stimulate their growth and development. Various reasons for parents in choosing a school must be adjusted to the situation and conditions they experience. On the other hand, the reasons for this consideration can be used as reference material for school principals in developing their schools. Data collection used an online survey with 39 respondents. The results of his research are that the distance between school and place of residence is the reason that dominates parents choosing a school for their children, although the other reasons are not much different in presentation. But other things that need attention for school principals are competitors of similar schools, the age of school children around the school, parents' perceptions of the importance of getting early childhood education, especially kindergarten. In addition, the regulations for granting operational permits for kindergartens by authorized agencies must pay attention to the number of similar schools in the area, this is due to avoid schools going out of business due to not having students.